PENGARUH MOTIVASI KERJA DAN KONDISI KERJA TERHADAP KEPUASAN KERJA KARYAWAN - . Priatno (Paradigma, 2014)
The research aims to know the influence of work motivation and working conditions toward the job satisfaction of employees of PT. Sentana Mitra Kualita. Data analysis being technic used is qualitative analysis. The results show that there is a positive influence between working motivation towards work satisfaction, and working condition toward work satisfaction. The technique of sampling used is Stratified Random Sampling. The results of the research show that the motivation factors have a significant influence on employee work satisfaction variables, indicates that the higher  motivation factors is given will the work employees increase employees satification of the employess. Work environment, level of education, wishes and needs are enough influence on employee work satisfaction. Partially the employees variabel needs are the dominant influence on work satisfaction, while the work environment education level variable are less significant toward employees satification.